The Changes of University Students Academic Motivation over Time: the Relationship with Academic Achievement, Satisfaction with Studies and Psychological Well-Being - Rugevičius, Mindaugas; Kairys, Antanas; Čepienė, Ramutė; Liniauskaitė, Audronė; Brazdeikienė, Liana; Žakaitis, Povilas (Pedagogika, 2020)
One of the most important psychological factors related to the success of studies is the students’ academic motivation. This study examined one-year changes in academic motivation, students’ satisfaction, and psychological well-being. Three hypotheses formulated: (1) Students’ motivation will decrease over the year, but it will be possible to distinguish the groups of students that will have different changes of motivation. (2) The decrease in intrinsic motivation will be associated with lower academic achievement and lower satisfaction with studies. (3) The decrease in intrinsic motivation will be associated with lower psychological well-being. The first measurement performed during the spring semester, the second performed 12 ± 1 months later. 232 fully completed two-measurement questionnaires were selected for the analysis. The sample included 52 men and 180 women. The Student Academic Motivation Scale (SAMS-21) was used to assess academic motivation, and the Lithuanian Psychological Well-being Scale for Young People (LPGS-J) was used to measure psychological well-being. It was found that during one-year academic motivation decreased and it showed very large individual differences. Changes in academic motivation, students’ satisfaction, and psychological well-being are interrelated, and changes in motivation allow one to predict study satisfaction and psychological well-being. The assumption that changes in motivation would predict students’ academic achievement not confirmed.